Dynamics of yield and nutritional value for winter forage intercropping - doi: 10.4025/actascianimsci.v34i2.11507 - Paris, Wagner; Marchesan, Renato; Cecato, Ulysses; Martin, Thomas Newton; Ziech, Magnos Fernando; Borges, Gisele Silveira (Acta Scientiarum. Animal Sciences, 2011)
The work was carried out to assess mass production and nutritional content of winter forages using lopsided oat (Avena strigosa) and white oat (Avena sativa) intercropped with ryegrass (Lolium multiflorum) and vetch (Vicia sativa L.). The species were intercropped as the following treatments: lopsided oat with ryegrass (LO+RG); white oat with ryegrass (CO+RG); lopsided oat with vetch (LO+V); white oat with vetch (CO+V); lopsided oat, vetch and ryegrass (LO+RG+V); and white oat, ryegrass and vetch (CO+RG+V). The study evaluated total forage mass production of each intercropping and crude protein levels, neutral detergent fiber and in vitro digestibility coefficient of dry matter. The results indicate that forage yield of oats was higher in early assessments, and ryegrass and vetch were higher in the final evaluation period. The crude protein levels and neutral detergent fiber were higher at the start of the experiment for all evaluated treatments, and those including vetch intercropped with oats showed an increase in these parameters in the final period due to the presence of vetch, which has a more delayed cycle.